Imaging response to immune checkpoint inhibitors in patients with advanced melanoma: a retrospective observational cohort study - Gupta, Mehul; Stukalin, Igor; Meyers, Daniel E.; Heng, Daniel Y. C.; Monzon, Jose; Cheng, Tina; Navani, Vishal (Frontiers in Oncology, 2024)
The association between objective imaging response and first line immune checkpoint inhibitor (ICI) therapy regimes in advanced melanoma remains uncharacterized in routine practice.We conducted a multi-center retrospective cohort analysis of advanced melanoma patients receiving first line ICI therapy from August 2013-May 2020 in Alberta, Canada. The primary outcome was likelihood of RECIST v1.1 assessed objective imaging response between patients receiving antiprogrammed cell death protein 1 (anti-PD1) monotherapy and those receiving combination ipilimumabnivolumab. Secondary outcomes were identification of baseline characteristics associated with nonresponse and the association of imaging response with overall survival (OS) and time to next treatment (TTNT).Results: 198 patients were included, 41/198 (20.7%) had complete response, 86/198 (43.4%) had partial response, 23/198 (11.6%) had stable disease, and 48/198 (24.2%) had progressive disease. Median OS was not reached (NR) (95% CI 49.0-NR) months for complete responders, NR (95%CI 52.9-NR) months for partial responders, 33.7 (95%CI 15.8-NR) months for stable disease, and 6.4 (95%CI 5.2-10.1) months for progressive disease (log-rank p<0.001). Likelihood of objective imaging response remained similar between anti-PD1 monotherapy and ipilimumab-nivolumab groups (OR 1.95 95%CI 0.85-4.63, p=0.121).Elevated LDH level (OR 0.46; 95%CI 0.21-0.98, p=0.043), mucosal primary site (OR 0.14; 95%CI 0.03-0.48, p=0.003), and BRAF V600E mutation status (OR 0.31; 95%CI 0.13-0.72, p=0.007) were associated with decreased likelihood of response.No significant difference in likelihood of imaging response between anti-PD1 monotherapy and combination ipilimumab-nivolumab was observed. Elevated LDH level, mucosal primary site, and BRAF V600E mutation status were associated with decreased likelihood of response. Given that pivotal clinical trials of ipilimumab-nivolumab did not formally compare ipilimumab-nivolumab with nivolumab monotherapy, this work adds context to differences in outcomes when these agents are used. These results may inform treatment selection, and aid in counseling of patients treated with first-line ICI therapy in routine clinical practice settings.